Preoperative Platelet-Lymphocyte Ratio as a Prognostic Factor of Epithelial Ovarian Cancer - Winata, Johan; Laihad, Bismarck Joel; Wagey, Frank Mitchell Marvel (Indonesian Socety of Obstetrics and Gynecology, 2023)
Objective: To determine whether platelet-lymphocyte ratio can be a prognostic factor for epithelial ovarian cancer. Methods: This study was a retrospective cohort with analytical design, conducted in the Department of Obstetrics and Gynecology of Prof. Dr. R.D. Kandou Manado General Hospital from January – November 2020. The subjects were all patients with epithelial ovarian cancer who met the inclusion and exclusion criteria. Data analysis was conducted with Chi-square test.Results: 35 subjects were included in this study. Most subjects were 40-50 years and had a platelet-lymphocyte ratio of above 200. The mean platelet-lymphocyte ratio of the subjects with epithelial ovarian cancer was 244.663 +- 130.0234. Chi-square test showed a significant association between platelet-lymphocyte ratio and the ovarian cancer relapse (X2 = 14.464 p = 0.000) with RR=4.0Conclusion: There was a significant difference between platelet-lymphocyte ratio and the ovarian cancer relapse.Keywords: epithelial ovarian cancer, inflammatory marker, platelet-lymphocyte ratio, prognosis.